Mixed Macroeconomic Performance of Nepal - Basyal, Tula Raj (Socio-Economic Development Panorama, 2008)
Nepal continues to remain an Least Developed Country (LDC) with a per capita income of around US $ 300. The structure of the economy is fragile, the economic environment is not favorable, the performance of the economy is weak and the development indicators of the country are unfavorable. The economic problems and development challenges have remained as daunting as have been the efforts and measures required to mitigate them. The economy has mainly been characterized by a period of political transition and uncertain economic environment on account of the predominance of the non-economic factors in the economy. While the important sectors of the economy experienced slowdowns, imbalances, and even uncertainties, no clear symptoms so far appear to indicate the emergence of economic revival. Supply factors and constraints in supply management at times threatened the goal of price stability. Though there was sluggish output growth and higher inflation that portrayed symptoms of stagflation, the macroeconomic stability was not under threat even in such a difficult period, especially because of the prudence in fiscal management and the overall surplus situation in the external account. Socio-Economic Development Panorama, Vol. 1. No. 2(2007) pp. 29-34